Men too sometimes shy away from competition: The case of team competition - Marie-Pierre Dargnies (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
Recent results in experimental and personnel economics indicate that women do not like competitive environments as much as men. This article presents an experimental design giving participants the opportunity to enter a tournament as part of a team rather than alone. While a large and significant gender gap in entry in the individual tournament is found in line with the literature, no gender gap is found in entry in the team tournament. Women do not enter the tournament significantly more often when it is team-based but men enter significantly less when they are part of a team rather than alone. The main reason for men's disaffection for the team competition appears to be linked to the uncertainty on their teammate's ability. More precisely, high-performing men fear to be the victims of the free-riding behaviour of their teammate.
Keywords: 330; Teams; Gender Gap; Tournament